Composite material as well as preparation method and application thereof

By forming a high-entropy oxide cover layer on the CoP substrate and introducing Cu and Ce elements, the problems of insufficient corrosion resistance and performance attenuation in practical applications of high-entropy alloy catalysts are solved, and efficient hydrogen evolution catalysis and good corrosion resistance are achieved. sex.

CN119455996APending Publication Date: 2025-02-18WUYI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In practical applications, existing high-entropy alloy catalysts have problems such as insufficient corrosion resistance and rapid attenuation of performance over time, making it difficult to have excellent electrochemical activity and excellent corrosion resistance.

Method used

CoP is used as the substrate, and a high-entropy oxide cover is formed on its surface through electrodeposition technology. Combining Cu and Ce elements, the electronic structure and chemical properties of the material are optimized, thereby improving catalytic activity and corrosion resistance.

Benefits of technology

It realizes the catalytic activity of efficient hydrogen evolution reaction at a low overpotential, and has good corrosion resistance and structural stability, which extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455996A_ABST
    Figure CN119455996A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method and application thereof, the composite material comprises a CoP substrate, a high-entropy oxide is formed on the CoP substrate, the high-entropy oxide is composed of metal elements and non-metal elements, the metal elements comprise Fe, Co, Ni, Cu and Ce, and the non-metal elements comprise O. The composite material developed by the invention takes CoP as a substrate, is fused with the high-entropy oxide and optimized elements such as Cu and Ce, and shows remarkable advantages in the field of clean energy conversion such as hydrogen production by electrolysis of water. The material not only has excellent electrocatalytic activity, can realize efficient hydrogen precipitation under lower overpotential, but also has good corrosion resistance and structural stability. Due to the characteristics, the composite material becomes a technical solution with great potential in hydrogen energy economic development, and is expected to provide powerful support for wide application of clean energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] As the world pays more and more attention to energy conservation, emission reduction and sustainable development, hydrogen energy, with its high energy conversion efficiency and zero-emission end product, is seen as one of the key ways to replace fossil fuels and promote greener energy transformation in the future. As an ideal clean energy, the development and utilization of hydrogen energy is of great significance to promoting the construction of an environmentally friendly society. Water electrolysis, especially electrolysis using electricity generated by renewable energy, is a highly promising method for producing high-purity hydrogen energy. It can not only reduce dependence on traditional energy, but also effectively integrate the intermittent nature of renewable energy.

[0003] However, although precious metal catalysts have long dominated the field of hydrogen production and are highly praised for their efficient catalytic activity, their high cost and relatively low product yield limit their large-scale commercial application and become a major obstacle to the popularization of hydrogen economy. In view of this, researchers are actively exploring and developing a variety of non-precious metal or low-cost alternative catalysts including phosphides, borides, metal oxides and metal hydroxides, in order to significantly reduce production costs while maintaining or improving catalytic efficiency.

[0004] Among these alternative catalyst systems, multi-component catalysts, especially those composite catalysts prepared by finely controlling the ratio of different elements, have demonstrated superior catalytic performance that exceeds that of single transition metal or traditional binary alloy catalysts. This performance improvement is mainly attributed to the synergistic effect between the components, which not only significantly enhances the catalytic active sites, but also effectively optimizes the electrical conductivity of the material, thereby greatly accelerating the process of the electrochemical reaction. It is particularly worth mentioning that high-entropy alloys (HEA), as a new type of multi-principal alloy material, have demonstrated extraordinary performance potential in the field of electrochemistry with their unique high entropy effect, slow diffusion effect, lattice distortion effect and "cocktail" effect, providing a new perspective and possibility for the development of high-performance catalysts.

[0005] However, despite the many theoretical advantages of high entropy alloy catalysts, they still face many challenges in practical applications, such as insufficient corrosion resistance and rapid performance degradation over time. Therefore, the development of a new composite material with both excellent electrochemical activity and excellent corrosion resistance is of great significance to promote the development of the field of electrochemical catalysis. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a composite material which not only has high catalytic activity but also has strong corrosion resistance.

[0007] The invention also provides a method for preparing the composite material.

[0008] The invention also proposes application of the composite material.

[0009] According to the first aspect of the present invention, the composite material includes a CoP substrate, on which a high entropy oxide is formed, and the high entropy oxide is composed of metal elements and non-metal elements, wherein the metal elements include Fe, Co, Ni, Cu and Ce, and the non-metal elements include O.

[0010] The composite material according to the embodiment of the present invention has at least the following beneficial effects: the present invention innovatively proposes a composite material design, which uses cobalt phosphide (CoP) as a substrate. On this basis, through careful regulation, a variety of metal elements react chemically with oxygen on the surface of the CoP substrate to form a unique high entropy oxide covering layer. The formation of this high entropy oxide layer not only significantly increases the specific surface area of ​​the material, but also the complex interaction between the elements inside it brings a unique electronic structure and chemical properties, thereby optimizing the adsorption and desorption process of the reaction intermediates on the catalyst surface. The synergistic effect of multiple elements greatly enhances the activity of the catalyst, allowing the hydrogen evolution reaction to be carried out efficiently under lower overpotential conditions. For example, the copper (Cu) and cerium (Ce) elements introduced into the high entropy oxide system, the introduction of Cu and Ce effectively enhances the corrosion resistance of the electrode, reduces the adsorption energy during the reaction, significantly improves the electrochemical hydrogen evolution reaction activity of the phosphide material, accelerates the reaction kinetics, and further improves the hydrogen evolution efficiency.

[0011] In addition, the difference in atomic size that makes up the high-entropy oxide leads to the random distribution of metal atoms in the lattice, forming a lattice distortion effect. This effect not only enhances the structural stability of the material, but also enables the catalyst to maintain excellent performance stability during the long-term electrolysis of water to produce hydrogen, and is not prone to performance degradation. At the same time, specific elements in the high-entropy oxide (such as Ce) show excellent corrosion resistance, effectively resisting the corrosion effects in the electrolysis water environment, thereby significantly extending the service life of the catalyst.

[0012] In summary, the composite material developed by the present invention, which is based on CoP and integrates high entropy oxides and optimized elements such as Cu and Ce, has shown significant advantages in the field of clean energy conversion such as water electrolysis to produce hydrogen. This material not only has excellent electrocatalytic activity, can achieve efficient hydrogen evolution at a low overpotential, but also has good corrosion resistance and structural stability. These characteristics make this composite material a highly potential technical solution in the development of the hydrogen energy economy, and it is expected to provide strong support for the widespread application of clean energy.

[0013] According to some embodiments of the present invention, the loading amount of the high entropy metal oxide on the CoP substrate is 0.71 mg / cm 2 above.

[0014] According to some embodiments of the present invention, the loading amount of the high entropy metal oxide on the CoP substrate is 2.77 mg / cm 2 above.

[0015] According to some embodiments of the present invention, the loading amount of the high entropy metal oxide on the CoP substrate is 4.6 mg / cm 2 above.

[0016] According to some embodiments of the present invention, the molar ratio of metal elements to O in the high entropy oxide is 1 to 2: 1. Preferably, it is 1.5 to 1.65: 1. According to some embodiments of the present invention, the molar ratio of Fe, Co, Ni, Cu and Ce in the high entropy oxide is 1: 1.5 to 3.5: 1.2 to 3: 2 to 4.5: 1 to 2. By adjusting the composition and element ratio of the high entropy oxide, the performance of the catalyst can be further optimized.

[0017] According to some embodiments of the present invention, in the CoP substrate, the CoP particles are distributed in the form of a nanoneedle array. When the CoP with a nanoneedle array structure is used as a substrate material, its special geometric morphology and physical properties have a significant impact on the subsequent electrodeposition process. First, the rich surface defects and active sites provided by the nanoneedle array are conducive to the adsorption and reduction of metal ions during the electrodeposition process, and promote the uniform deposition of metal oxides on the CoP surface. Secondly, the directional arrangement and high order of the nanoneedle array help guide the growth direction of the electrodeposition product, so that the formed metal oxide layer has a specific structure and composition.

[0018] According to some embodiments of the present invention, the composite material further comprises a porous conductive support material, and the CoP substrate is supported on the porous conductive support material.

[0019] According to some embodiments of the present invention, the porous conductive support material includes nickel foam or carbon cloth.

[0020] According to some embodiments of the present invention, the porous conductive carrier material is nickel foam. Nickel foam has a large specific surface area, can load more effective ingredients and has good conductivity. When nickel foam is used as a carrier, the prepared composite material has better hydrogen evolution catalytic performance.

[0021] The preparation method according to the second aspect of the present invention comprises the following steps:

[0022] Take Ni 2+ , Fe 3+ , Cu 2+ 、Co 2+ 、Ce 3+ 、H2PO2 - A solution of is used as an electrolyte, and a high entropy oxide is formed on the CoP substrate by electrodeposition.

[0023] The preparation method according to the embodiment of the present invention has at least the following beneficial effects: the preparation method of the scheme of the present invention cleverly adopts a simple and efficient electrodeposition technology to achieve the synthesis of the above-mentioned high-performance composite material. The core advantage of this preparation strategy is that it completely abandons the dangerous chemical reagents commonly used in traditional synthesis methods, such as sodium borohydride, hydrazine hydrate, etc. These reagents are often highly toxic and flammable and explosive, which brings great safety hazards to experimental operations. In contrast, the preparation method of the present invention not only avoids these risks, but also significantly simplifies the synthesis steps, making the whole process more gentle, safe and easy to control.

[0024] During the electrodeposition process, the CoP substrate can uniformly and efficiently adsorb and fix a variety of metal ions. Subsequently, under appropriate oxidation conditions, these metal ions react with oxygen to form a high-entropy oxide coating with a dense structure and uniform composition in situ on the CoP surface. In this process, hypophosphite acts as a reducing agent in the electrolyte and also has the function of regulating the pH value of the electrolyte.

[0025] The entire preparation process is not only easy to operate and does not require complex and expensive equipment, but is also environmentally friendly and reduces the generation of hazardous waste. In addition, due to the rapid responsiveness and high controllability of the electrodeposition technology, the composite material of the present invention can be synthesized on a large scale and with high quality in a short period of time, which is of great significance for promoting its practical application in energy conversion fields such as water electrolysis to produce hydrogen.

[0026] In summary, the composite material preparation method based on electrodeposition technology proposed in the present invention not only overcomes many limitations of traditional synthesis methods, but also provides a practical solution for the large-scale production of high-performance phosphide-based composite materials with its simplicity, safety and efficiency, injecting new vitality into the development of the hydrogen energy economy.

[0027] According to some embodiments of the present invention, Ni in the solution 2+ , Fe 3+ , Cu 2+ 、Co 2+ 、Ce 3+ 、H2PO2 - The molar ratio is 1: 0.5~1.5: 0.5~1.5: 0.5~1.5: 0.5~1.5: 0.2~0.3. By accurately matching the metal ion source, it is ensured that the metal ions can be evenly distributed in the high entropy oxide, so as to play their unique role in improving corrosion resistance and reducing adsorption energy.

[0028] According to some embodiments of the present invention, Ni in the solution 2+ , Fe 3+ , Cu 2+ 、Co 2+ 、Ce 3+ 、H2PO2 - The molar ratio is 1:1:1:1:1:0.26.

[0029] According to some embodiments of the present invention, the electrodeposition conditions include at least one of the following conditions: 1) the electrodeposition time is 1 to 10 min; 2) the voltage is -0.9 V to -1.22 V; 3) the current density is 15 to 20 mA cm -2 ; 4) pH is 3-4.

[0030] According to some embodiments of the present invention, the electrodeposition time is more than 3 minutes, such as 5 minutes.

[0031] According to some embodiments of the present invention, the CoP substrate is prepared by hydrothermal or vapor deposition. By hydrothermal or vapor deposition technology, a CoP with a nanoneedle array structure can be prepared. When the CoP with this nanoneedle array structure is used as a substrate material, its special geometric morphology and physical properties have a significant impact on the subsequent electrodeposition process. First, the rich surface defects and active sites provided by the nanoneedle array are conducive to the adsorption and reduction of metal ions during the electrodeposition process, and promote the uniform deposition of metal oxides on the CoP surface. Secondly, the directional arrangement and high order of the nanoneedle array help to guide the growth direction of the electrodeposition product, so that the formed metal oxide layer has a specific structure and composition.

[0032] According to some embodiments of the present invention, the preparation process of the CoP substrate comprises the following steps:

[0033] Take a porous conductive carrier material and a Co-containing 2+ 、F -and a reducing agent solution through a hydrothermal method to grow Co(OH)2 on the surface of a porous conductive support material; and phosphating Co(OH)2 to obtain CoP supported on the porous conductive support material.

[0034] According to some embodiments of the present invention, the Co 2+ 、F - The molar ratio of the reducing agent is 6:4-5:2.5-3.5.

[0035] According to some embodiments of the present invention, the reducing agent includes at least one of urea or glucose. Urea or glucose is used to reduce metal ions.

[0036] According to some embodiments of the present invention, the F - Added in the form of ammonium fluoride. Adding a fluorine source allows the substrate to be etched using fluorine ions to control the morphology.

[0037] According to some embodiments of the present invention, the reaction temperature of the hydrothermal method is 110-130° C. and / or the reaction time is 4-8 hours. For example, the reaction temperature is 120° C. and the reaction time is 6 hours.

[0038] According to some embodiments of the present invention, the phosphating specifically includes the following operations: continuously introducing an inert gas flow, placing hypophosphite upstream of the inert gas flow, and placing a porous conductive carrier material with Co(OH)2 grown on the surface downstream; the phosphating process is carried out at 300-400° C. Red phosphorus can also be used as a phosphating agent, and the use of hypophosphite is safer.

[0039] According to some embodiments of the present invention, the ratio of the mass of the hypophosphite to the molar amount of CoP is 0.25 g:1 mol to 1.7 g:1 mol.

[0040] According to some embodiments of the present invention, the phosphating process is kept at 300-400° C. for 1-3 hours.

[0041] According to some embodiments of the present invention, the phosphating process is kept at 340-360° C. for 1-3 hours. For example, the reaction temperature is 350° C. and the time is 2 hours.

[0042] According to some embodiments of the present invention, the heating rate of the phosphating process is 4-6°C / min, such as 5°C / min.

[0043] According to some embodiments of the present invention, the preparation method further comprises the step of annealing the composite material.

[0044] According to some embodiments of the present invention, the annealing temperature is 180-220° C., and / or the time is 45-75 min. For example, the annealing temperature is 200° C., and / or the time is 60 min.

[0045] According to the application of the third aspect of the embodiment of the present invention, a catalyst comprises the above-mentioned composite material.

[0046] Application of the composite material or the catalyst in electrolysis of water.

[0047] According to the application of the embodiment of the present invention, at least the following beneficial effects are achieved: the composite material provided by the scheme of the present invention is based on CoP, and is integrated with high entropy oxides and optimized elements such as Cu and Ce. Its unique electronic structure and chemical properties make these materials not only have potential application value in the field of hydrogen production by electrolysis of water, but also may play a role in other energy conversion fields (such as fuel cells, metal-air batteries, etc.). When used as a catalyst such as hydrogen evolution, the composite material exhibits excellent electrocatalytic activity in the electrochemical hydrogen evolution reaction, and also has good corrosion resistance, which is crucial for the long-term operation of the hydrogen production system by electrolysis of water. Good corrosion resistance means less maintenance and replacement requirements, thereby reducing the overall operating cost of the system. Its high electrocatalytic activity makes the process of hydrogen production by electrolysis of water more efficient, thereby improving the efficiency of the entire energy conversion system. As a clean and efficient energy carrier, the widespread application of hydrogen energy will strongly promote the development of the hydrogen energy economy. The emergence of this composite material provides a more reliable and efficient catalyst selection for the production of hydrogen energy.

[0048] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0050] Figure 1 It is a comparison chart of XRD characterization results of the composite materials, some intermediate products and raw material NF prepared in Example 1 and Comparative Example 4 of the present invention.

[0051] Figure 2 This is a comparison diagram of SEM characterization results of the composite material prepared in Example 1 of the present invention and the carrier loaded with a substrate prepared before the electrodeposition treatment.

[0052] Figure 3 It is a comparison chart of the test results of the hydrogen evolution catalytic performance of Examples 1 to 3 of the present invention and Comparative Example 4.

[0053] Figure 4It is a comparison chart of the test results of the hydrogen evolution catalytic performance of Examples 1 and 4 of the present invention and Comparative Example 4.

[0054] Figure 5 It is a comparison chart of the test results of the hydrogen evolution catalytic performance of Example 1 of the present invention and Comparative Examples 1 to 4.

[0055] Figure 6 This is a physical picture of the working electrode after the test of Comparative Example 1 of the present invention is completed.

[0056] Figure 7 This is a physical picture of the working electrode after the test of Comparative Example 3 of the present invention is completed. DETAILED DESCRIPTION

[0057] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0058] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0059] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0060] The "room temperature" referred to in the present invention refers to 20-25°C, and specifically 25°C in the embodiments.

[0061] Example 1

[0062] This example provides a composite material, which is composed of a nickel foam carrier, a CoP substrate and a high entropy oxide layer in sequence, wherein the CoP substrate is loaded on the nickel foam carrier, and a high entropy oxide is formed on the CoP substrate. The high entropy oxide is composed of metal elements and non-metal elements, wherein the metal elements are Fe, Co, Ni, Cu and Ce, and the non-metal element is O. The preparation thereof comprises the following steps:

[0063] Take a nickel foam (NF) with a size of 2cm*4cm (length*width) and use deionized water, 6mol / L hydrochloric acid, and anhydrous ethanol to ultrasonically clean the surface oxide for 5 minutes respectively. Dissolve 0.6mol Co(NO3)·6H2O, 0.47mol NH4F, and 0.29mol CH4N2O in 30mL of deionized water and stir until the solution is clear. Put the above-configured solution and the cleaned nickel foam into a 50mL high-pressure reactor and put it into an oven. The reaction temperature is 120℃ for 6h to grow Co(OH)2 on the nickel foam. Dry the obtained Co(OH)2 in an argon atmosphere, then take 1g of sodium hypophosphite and put it into the upstream of the tube furnace, put Co(OH)2 into the downstream of the tube furnace, and keep it at 350℃ for 2h (heating rate 5℃ / min) under argon flow to phosphate Co(OH)2 to obtain CoP. 5 mmol of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Ce(NO3)3·6H2O and 150 mg of sodium hypophosphite were dissolved in 50 mL of deionized water, stirred until clear, and prepared into an electrolyte. The electrolyte was subjected to constant voltage (-1 V, current density of 15-20 mA cm) under a three-electrode system (working electrode: CoP / NF, counter electrode: platinum mesh, reference electrode: calomel electrode). -2 The FeCoNiCuCe / CoP / NF was dried at room temperature and then annealed at 200°C for 60 minutes in an air atmosphere in a tube furnace.

[0064] Example 2

[0065] This example provides a composite material, which differs from Example 1 only in that the constant voltage electrodeposition time is changed to 3 minutes, and the obtained sample is named FeCoNiCuCe / CoP / NF-3.

[0066] Example 3

[0067] This example provides a composite material, which differs from Example 1 only in that the constant voltage electrodeposition time is changed to 1 minute, and the obtained sample is named FeCoNiCuCe / CoP / NF-1.

[0068] Example 4

[0069] This example provides a composite material, which differs from Example 1 only in that, except for no annealing, the rest of the preparation and testing methods are the same as those of Example 1, and the obtained sample is named FeCoNiCuCe / CoP / NF-m.

[0070] Comparative Example 1

[0071] This example provides a composite material, which differs from Example 1 only in that Ce(NO3)3·6H2O is not added during the electrodeposition process, and the sample is named FeCoNiCu / CoP / NF.

[0072] Comparative Example 2

[0073] This example provides a composite material, which differs from Example 1 only in that Cu(NO3)2·3H2O and Ce(NO3)3·6H2O are not added during the electrodeposition process, and the sample is named FeCoNi / CoP / NF.

[0074] Comparative Example 3

[0075] This example provides a composite material, which differs from Example 1 only in that Cu(NO3)3·6H2O is not added during the electrodeposition process, and the sample is named FeCoNiCe / CoP / NF.

[0076] Comparative Example 4

[0077] This example provides a composite material, which differs from Example 1 only in that no metal nitrate is added during the electrodeposition process, and the sample is named CoP / NF.

[0078] Test Case

[0079] In this example, the structure, morphology and performance of the composite materials prepared in the above examples and comparative examples were characterized and tested.

[0080] 1) Structural characterization

[0081] The structures of the composite materials prepared in the examples and comparative examples were characterized by X-ray powder diffractometer (XRD). The characterization results of the composite materials prepared in Example 1 and Comparative Example 4, the phosphated CoP in Example 1, and the nickel foam as a raw material are shown in FIG. Figure 1 As shown in the figure, the diffraction peaks of nickel foam are at 44.604, 51.97 and 76.588, respectively, representing the crystal planes (111), (200) and (220) of nickel foam. Since the diffraction peaks of nickel foam have a high peak intensity between 40 and 90, it is difficult to observe the complete crystal plane of CoP. Only the diffraction peak of CoP can be observed at 31.093, indicating the crystal plane (110) of CoP.

[0082] By comparison, it was found that after FeCoNiCuCe high entropy oxide was loaded on CoP / NF, its peak intensity was significantly enhanced, indicating that the loaded material had a higher degree of crystallinity. In addition, the loading of high entropy oxide also caused the CoP diffraction peak to shift toward a small angle. According to the Bragg equation 2dsinθ=nλ, the decrease in the diffraction angle means that the interlayer spacing of CoP as the substrate increases. This increase in interlayer spacing in turn leads to an increase in the specific surface area of ​​the material.

[0083] 2) Morphological characterization

[0084] To further verify the XRD results, the prepared composite material was characterized by scanning electron microscopy (SEM). The characterization results of the composite material prepared in Example 1 and the carrier loaded with the substrate prepared before the electrodeposition treatment are as follows: Figure 2 As shown in the figure, through electrodeposition and annealing at 200℃, a coral-like morphology is formed on the CoP / NF surface on the needle array of CoP / NF, which greatly increases the active area.

[0085] 3) Performance Characterization

[0086] The composite materials prepared in the above embodiments and comparative examples were tested and characterized for their catalytic hydrogen evolution performance. The specific operation process is as follows: (1) The working electrode uses a platinum electrode clip so that it is just immersed in the electrolyte. (2) Hydrogen evolution performance test: The material of the platinum electrode is used as the working electrode, mercury / mercuric oxide is used as the reference electrode, the platinum mesh is used as the counter electrode, and the 1M KOH aqueous solution is used as the electrolyte. The hydrogen evolution test is carried out in an electrochemical workstation, and the LSV (linear sweep voltammetry) test is performed 6 times. During the test, the current density is 100mAcm -2 The hydrogen evolution catalytic performance was evaluated through polarization curve testing.

[0087] As the electrodeposition time increases, the loading amount of the high entropy metal oxide also increases. The loading amount of Example 1 is 4.6 mg / cm -2 Example 2: Loading capacity: 2.77 mg / cm -2 Example 3: Loading amount is 0.71 mg / cm -2 In order to investigate the effect of the anti-electrodeposition time on the hydrogen evolution performance, the test results of Examples 1 to 3 and Comparative Example 4 were compared. Figure 3 As shown in the figure, compared with the original CoP, Example 1 obviously shows better catalytic performance for hydrogen evolution reaction. At the same time, due to the increase of electrodeposition time, the number of active sites on the surface increases, and the overpotential also decreases accordingly. -2 The corresponding hydrogen evolution overpotentials are 276 mV, 314 mV, 385 mV and 426 mV, respectively.

[0088] In order to investigate the effect of annealing on the hydrogen evolution performance of high entropy oxide, the test results of Example 1, Example 4 and Comparative Example 4 were compared. Example 1 and Example 4 are composite materials of FeCoNiCuCe / CoP / NF annealed in air atmosphere at 200°C and FeCoNiCuCe / CoP / NF without annealing treatment, respectively. The comparison results are as follows: Figure 4 As shown in the figure, it can be seen that Example 1 shows a better catalytic performance of oxygen evolution reaction than Example 4 and Comparative Example 4. -2 The corresponding oxygen evolution overpotentials are 276, 343, and 426 mV, respectively. This shows that annealing can make the metal ions deposited on the substrate material more evenly dispersed. This uniform dispersion not only optimizes the structure of the material, but also improves the accessibility of the catalytic active sites, thereby enhancing the catalytic efficiency of the hydrogen evolution reaction. Therefore, annealing can synergistically improve the hydrogen evolution performance of high entropy oxides.

[0089] In order to investigate the effects of Ce ions and Cu ions on the stability and hydrogen evolution performance of high entropy alloy catalysts, Ce ions, Cu ions and Ce or Cu ions were removed from FeCoNiCuCe / CoP / NF in Example 1 to prepare comparative examples 1 to 3. The results of Example 1 were compared with those of comparative examples 1 to 4. Figure 5 As shown in the figure, it can be seen that Example 1 shows a better catalytic performance for hydrogen evolution reaction than Comparative Examples 1, 2, and 3. -2 The corresponding hydrogen evolution overpotentials are 276, 326, 337 and 346 mV, respectively. It can be seen from this that this data shows that under the same conditions, when the catalyst does not contain Ce ions and / or Cu ions, the hydrogen evolution potential will increase significantly. Although these potential values ​​may still be at a low level relative to other non-optimized catalysts, further analysis of the electrolyte after the test found that when the catalyst lacks Cu ions and / or Ce ions, the interfacial stability of the electrode drops sharply, and even dissolution occurs. This observation is particularly evident in the electrolytes of Comparative Example 1 (lack of Cu ions) and Comparative Example 3 (lack of both Cu ions and Ce ions), as shown in Figure 2. Figure 6 and 7 These images intuitively show the dissolution of the electrode interface in the absence of these key ions, proving that the introduction of Cu and Ce ions is essential for maintaining the stability of the electrode surface. In addition, the two show a synergistic effect in maintaining the stable performance of the electrode, that is, their co-existence can more effectively stabilize the electrode interface.

[0090] The measured overpotential data of the composite materials of each embodiment and comparative example are summarized in the following Table 1:

[0091] Table 1

[0092] Overpotential mV Example 1 276 Example 2 314 Example 3 385 Example 4 343 Comparative Example 1 326 Comparative Example 2 337 Comparative Example 3 346 Comparative Example 4 426

[0093] It can be seen from Table 1 that the composite material prepared according to the embodiment of the present invention has good hydrogen evolution catalytic activity.

[0094] The composite material preparation scheme proposed in the embodiment of the present invention has significant advantages: the raw materials are simple and easy to obtain, the process flow is streamlined and efficient, and it is convenient for large-scale production. The entire reaction process is green and environmentally friendly, and there is no toxic emission. By adjusting the electrodeposition time, the loading amount of high entropy metal in the FeCoNiCuCe / CoP / NF composite material can be flexibly controlled, and the operation is simple and easy. This composite material is applied to the hydrogen evolution reaction, showing excellent catalytic activity and good stability.

[0095] During the preparation process, a hydrothermal method was first used to prepare CoP with a nanoneedle array structure as a substrate. This special geometric morphology and physical properties have a positive impact on the subsequent electrodeposition process. The rich surface defects and active sites provided by the nanoneedle array are conducive to the adsorption and reduction of metal ions, and promote the uniform deposition of metal oxides on the CoP surface. At the same time, the directional arrangement and high order of the nanoneedle array effectively guide the growth direction of the electrodeposition product, so that the formed metal oxide layer has a specific structure and composition.

[0096] Furthermore, multiple metal elements were deposited on the CoP nanoneedle array by electrodeposition to form metal oxides with high entropy properties. High entropy oxides usually exhibit excellent catalytic performance and stability due to their complex composition, stable structure and rich catalytic active sites. The CoP nanoneedle array not only promotes the electrodeposition process, but also provides an ideal template for the formation of high entropy metal oxides. The formation of high entropy oxides not only significantly increases the specific surface area of ​​the material, but also the complex interaction between its internal elements brings about a unique electronic structure and chemical properties, thereby optimizing the adsorption and desorption process of reaction intermediates on the catalyst surface. The synergistic effect of multiple elements greatly enhances the activity of the catalyst, allowing the hydrogen evolution reaction to proceed efficiently at a lower overpotential. The copper (Cu) and cerium (Ce) elements introduced into the high entropy oxide system significantly enhance the corrosion resistance of the material and effectively reduce the adsorption energy during the reaction process, thereby significantly improving the electrochemical hydrogen evolution reaction activity of the phosphide material, accelerating the reaction kinetics, and further improving the hydrogen evolution efficiency.

[0097] In addition, the lattice distortion effect caused by the difference in atomic size that constitutes the high entropy oxide not only enhances the structural stability of the material, but also enables the catalyst to maintain excellent performance stability during the long-term electrolysis of water to produce hydrogen. At the same time, the excellent corrosion resistance exhibited by specific elements in the high entropy oxide (such as Ce) effectively resists the corrosion effects in the electrolysis water environment, thereby significantly extending the service life of the catalyst.

[0098] In summary, the composite material preparation scheme proposed in the present invention provides a new idea and method for developing high-performance electrocatalytic materials and has broad application prospects.

[0099] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A composite material, characterized in that: It includes a CoP substrate, on which a high entropy oxide is formed, and the high entropy oxide is composed of metal elements and non-metal elements, wherein the metal elements include Fe, Co, Ni, Cu and Ce, and the non-metal elements include O.

2. The composite material according to claim 1, characterized in that: The material relationship in the composite material satisfies at least one of the following conditions: 1) The loading amount of high entropy metal oxide on CoP substrate is 0.71 mg / cm 2 Above; preferably, at 2.77mg / cm 2 More preferably, at 4.6 mg / cm 2 above; 2) The molar ratio of the metal element to O in the high entropy oxide is 1 to 2:1; 3) The molar ratio of Fe, Co, Ni, Cu and Ce in the high entropy oxide is 1:1.5-3.5:1.2-3:2-4.5:1-2.

3. The composite material according to claim 1, characterized in that: In the CoP substrate, CoP particles are distributed in the form of nano-needle arrays.

4. The composite material according to any one of claims 1 to 3, characterized in that: The composite material further comprises a porous conductive support material, and the CoP substrate is loaded on the porous conductive support material; preferably, the porous conductive support material comprises foamed nickel or carbon cloth.

5. The method for preparing a composite material according to any one of claims 1 to 4, characterized in that: The steps include: Take Ni 2+ , Fe 3+ , Cu 2+ 、Co 2+ 、Ce 3+ 、H2PO2 - A solution of is used as an electrolyte, and a high entropy oxide is formed on the CoP substrate by electrodeposition.

6. The preparation method according to claim 5, characterized in that: The electrodeposition conditions include at least one of the following conditions: 1) Ni in the solution 2+ , Fe 3+ , Cu 2+ 、Co 2+ 、Ce 3+ 、H2PO2 - The molar ratio is 1: 0.5-1.5: 0.5-1.5: 0.5-1.5: 0.5-1.5: 0.2-0.3; 2) the electrodeposition time is 1-10 min; 3) the voltage is -0.9 V to -1.22 V; 4) the current density is 15-20 mA cm -2 ; 5) pH is 3-4.

7. The preparation method according to claim 5, characterized in that: The CoP substrate is prepared by hydrothermal or vapor deposition method; preferably, the preparation process of the CoP substrate comprises the following steps: taking a porous conductive carrier material and a Co-containing 2+ 、F - and a reducing agent solution to grow Co(OH)2 on the surface of a porous conductive support material by a hydrothermal method; phosphating Co(OH)2 to obtain CoP supported on the porous conductive support material; more preferably, the preparation process of the CoP substrate includes at least one of the following conditions: 1) The Co 2+ 、F - The molar ratio of the reducing agent is 6:4-5:2.5-3.5; 2) The reaction temperature of the hydrothermal method is 110-130° C.; and / or the reaction time is 4-8 hours; 3) The phosphating process specifically includes the following operations: continuously introducing an inert gas flow, placing hypophosphite upstream of the inert gas flow, and placing a porous conductive carrier material with Co(OH)2 grown on the surface downstream; the phosphating process is carried out at 300-400°C; 4) The reducing agent includes at least one of urea or glucose.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method further comprises the step of annealing the composite material; preferably, the annealing temperature is 180-220° C., and / or the annealing time is 45-75 min.

9. A catalyst, characterized in that: The method comprises the composite material according to any one of claims 1 to 4.

10. Use of the composite material according to any one of claims 1 to 4 or the catalyst according to claim 9 in electrolysis of water.